The integrated microfluidic photocatalytic planar reactor under continuous operation - Ge, Xue-hui; Wei, Nanjie; Hu, Xinyue; Xie, Qinyin; Wang, Xiaoda; Li, Ling; Qiu, Ting (Frontiers in Chemical Engineering, 2024)
An integrated microfluidic planar reactor is essential for achieving efficient and enhanced photocatalytic water treatment. Optimization of catalysts is an area of intense study owing to the need to enhance the performances of microreactors. A high-efficiency photocatalytic microreactor is presented here by combining a planar microreactor with a high-efficiency photocatalyst. TiO2 nanoparticles doped with Y and Yb were prepared to improve the photocatalytic reaction efficiency. First, better performance is achieved with the Y, Yb/TiO2 and TiO2 microreactors than conventional bulk reactors because of good photodegradation and a high reaction rate. Then, the Y, Yb/TiO2 film microreactor exhibits not only efficient catalytic activity with UV light but also higher photocatalytic activity under visible light irradiation than that achieved by a TiO2 film microreactor. The reaction rate constant of the Y, Yb/TiO2 film microreactor is approximately 0.530 s–1, which is twice that of the TiO2 film microreactor. Moreover, the performances under continuous and intermittent reactions are compared to evaluate the stability of the microreactor, thereby building the foundation for practical application of continuous water treatment in the microreactor.The planar microreactor provides a convenient platform for studying photodegradation under various conditions, such as different temperatures, flow rates, light irradiation (UV and Vis), and reaction modes (continuous and intermittent).